The effect of eight weeks of high-intensity interval training with caloric restriction and spirulina supplementation on inflammatory factors in heart tissue of rats under high-fat diet - Jamshid Khirabadi; Zaher Etemad; Kamal Azizbeigi; khalid mohamadzadeh salamat (Shahid Beheshti University, 2023)
Background and Purpose: The increase of inflammatory factors following obesity is known as one of the main causes of mortality. Although the role of exercise training, caloric restriction and antioxidant supplements have been reported in this field; But their simultaneous effect is of interest to many researchers. Therefore, the aim of the present study was to investigate the effect of eight weeks of HIIT (High-intensity interval training) , calorie restriction and spirulina supplementation on inflammatory factors in the heart tissue of rats fed a high-fat diet.Materials and Methods: 45 obese male rats with a diet (60% fat, 20% protein, and 20% carbohydrate) were randomly divided into eight groups (1) high-calorie diet (HFD) (2) spirulina supplement (Sp), (3) caloric restriction (CR), (4) intense interval training (HIIT), (5) spirulina supplement - intense interval training (HIIT+Sp), (6) intense interval training - caloric restriction (CR+HIIT), (7) spirulina supplement-caloric restriction (CR+Sp), (8) intense interval training-caloric restriction-spirulina supplement (CR+HIIT+Sp). Also, five healthy rats were included in the healthy control group to investigate the effects of a high-calorie diet on the research variables. Intense interval training was performed for eight weeks, three sessions per week with an intensity of 80-110% of the maximum running speed and with 2-8 high intensity intervals, spirulina supplement 100 mg/kg/day was administered orally for eight weeks. Moreovwe, the caloric restriction groups used only 60% of the food consumed the previous day. To analyze the data, one-way analysis of variance was used along with Tukey's post hoc test (P ≤ 0.001).Results: The values of P38MAPK, NF-κB and TNF-α were higher in the HIIT group and significantly lower in the CR group than the HFD group (P ≤ 0.001). The levels of TNF-α in the spirulina supplement, spirulina supplement-intense central training and intense interval training-caloric restriction groups were significantly lower than the high-calorie diet group (P ≤ 0.001); The values ​​of NF-kB in the group of intense interval training-caloric restriction were significantly lower than those of the high-calorie diet (P ≤ 0.001). Also, in the severe interval marinade-caloric restriction-spirulina supplement group, NF-kB, TNF-α values ​​were significantly lower and P38MAPK was significantly higher than the high-calorie diet group (P≤0.001).Conclusion: It seems that caloric restriction and spirulina supplement alone have anti-inflammatory effects, although the anti-inflammatory effect of caloric restriction was somewhat higher than that of spirulina and HIIT; Therefore, the use of these two interventions, along with HIIT, is desirable for reducing inflammatory factors following obesity and overweight in animal models.